A critique of linguistic criticism: An applied study of the book (The Linguistic Structure of Al-Sayyab's Poetry) - سعيد, هاوكار عبدالرحمن; البرزنجي, دلسوز جعفر (Sulaimani Journal for Humanities, 2019)
This paper deals with a significant and current issue that is a linguistic critical criticism. The research will illustrate a brief perspective on the concept of linguistic criticism, and then it will particularly focus on the book of (Syntax of Peotry of Sayyab) that was written by Khalil Ibrahim Attiyah. The aim of this paper is to re-read the writer’s criticism of the language of Sayyab. The writer does not follow one academic approach in his critical work. Instead, he hardly criticizes some texts while in somewhere he is lenient towards those that should be strictly criticized. So it can be said that he successfully criticizes some texts while he is wrong towards some brilliant texts of Sayyab’ work.